Economic burden and its associates of childhood hand, foot, and mouth disease in Anhui province, 2018 - 2019 season: a cross-sectional survey - Wanwan MA; Lei GONG; Fang CHEN; Yongkang XIAO; Guoping CHEN; Sai HOU; Yuanfang SUN; Dandan SONG; Meng ZHU; Jiabing WU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo investigate the situation and influencing factors of the economic burden of childhood hand, foot, and mouth disease (HFMD) in Anhui province in the 2018 - 2019 season to provide evidence for health policy development. MethodsIn January 2018, 14 county-level and municipal hospitals in Anhui province were selected as research sites using a multistage stratified random sampling method. The information of 2 941 outpatients and hospitalized children with HFMD who visited the research site from January 2018 to December 2019 was collected by a combination of questionnaire survey, hospital billing system query, and telephone follow-up. The direct and indirect economic burden (median [M], 25th percentile, 75th percentile [P25, P75] in Chinese yuan) of children with HFMD was calculated, and the main influencing factors of the disease economic burden were analyzed. ResultsA total of 2 140 children with HFMD were included in the analysis, including 1 119 outpatients (52.3%) and 1 021 inpatients (47.7%). The direct economic burden of outpatients and inpatients was 216.0 (138.4, 339.0) yuan and 2 740.0 (1 870.6, 3 627.6) yuan, the indirect economic burden was 66.0 (0.0, 132.0) yuan and 264.0 (198.0, 429.0) yuan, and the total economic burden was 299.8 (216.0, 452.0) yuan and 3 088.4 (2 173.1, 4 072.9) yuan, respectively. The results of multivariate unconditional logistic regression analysis showed that the HFMD outpatients with higher average monthly family income were more likely to have a significantly higher total economic burden, but those who were kindergarten children and primary school students were more likely to have a significantly lower total economic burden; while the likelihood of having a higher total economic burden was significantly higher for HFMD inpatients aged 12 - 36 months, whose guardians had a college education and above, and with a hospitalization duration of 6 days and more. ConclusionChildhood HFMD can increase the economic burden of the patient's family and the society in Anhui province. The age, identity, average monthly family income, guardian's education level and hospitalization time are the main influencing factors of the economic burden.